Code Green: Money-Driven Hospitals and the Dismantling of Nursing - Jones, Esyllt (Labour / Le Travail, 2005)
The article reviews the book, "Code Green: Money-Driven Hospitals and the Dismantling of Nursing. Weinberg," by Beth Dana.